Numerical Study for a Marine Current Turbine Blade Performance under Varying Angle of Attack. (July 2017) - Dajani, S.; Shehadeh, M.; Saqr, K.M.; Elbatran, A.H.; Hart, N.; Soliman, A.; Cheshire, D.
Abstract: Energy generation from marine currents is a promising technology for sustainable development. The success of using marine current turbines to tap the ocean hydrodynamic energy depends on predicting the hydrodynamic characteristics and performance of such turbines. This paper presents an analysis of the two dimensional flow using commercial CFD software over a marine current turbine blade. The 2D flow is simulated for HF-SX NACA foil modified from S1210 NACA foil at various angles of attack with Reynolds number of 19×10 4, which represents the marine current flow. The hydrofoil is designed with considerations for lift and drag coefficients. The flow is simulated by solving the steady-state Navier-Stokes equations coupled with the k-ω shear stress transport (SST) turbulence model. The aim of this work is to study the effect of the angle of attack on the lift and drag coefficients. The computational domain is composed of non-homogenous structured meshing, with sufficient refinement of the domain near the foil blade in order to capture the boundary layer effects. Hence, all calculations are done at constant flow velocity while varying the angle attack for every model tested. The results have shown that the drag and lift coefficient, Cd and Cl coefficient increases with increasing the value of the angle of attack, ratio Cl /Cd curve related on performance at the peak 7° angle of attack.